Penswastaan institusi zakat dan kesannya terhadap pembayaran secara formal di Malaysia - Ahmad, Sanep; Wahid, Hairunnizam; Mohamad, Adnan (Universiti Utara Malaysia, 2006)
Leakages in zakat payment is widely discussed. Some individuals prefer to pay zakat directly to the asnaf or even pay zakat outside their locality. This practice has affected the efficiency of the collection and distribution of zakat. Although the presence of formal institutions such as PPZ and PPS have improved zakat management, this practice is still exist. The question is why is such practice still existing and what are the factors that influences individual into carrying out such practice. Thus this study examines the factors that influences the individual's dissatisfaction towards formal institutions in order to reduce leakages and increase zakat collection.The study utilizes primary data that can be analysed by using discriptive and logistic analysis. The result shows that satisfaction towards the zakat management significently influences individual compliance behaviour towards formal institutions.This indicates that to attract more people to formal institutions,they should first increase the individual satisfaction. This can be done by constantly improving zakat management, maintaining good will, becoming more transparent and conducting more productive distribution schemes.